ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study aims to determine the effect of variable ROE, EPS, PER, Size, and CR on stock prices in mining companies listed on the Indonesian Stock Exchange (BEI). The population is the entire mining company in Indonesia Stock Exchange (IDX) the number of 134 companies and the period of 2009-2012. Samples taken in this study were 95 companies that are not consecutive - participated. The sampling technique used was purposive sampling. The analytical tool used in this study is the Multiple Linear Regression Analysis. The results showed that the coefficient of determination in this study is the value of Adjusted R Square of 21.9%. As for the test statistic F-test shows that the ROE. EPS, PER, Size, and CR together - the same effect on stock prices. And partial hypothesis testing results show that there is a significant positive effect of EPS on stock prices. As for the ROE, Size and CR positive effect was not significant. Keywords: Return on Equity, Earnings Per Share, Price Earning Ratio, Size, Current Ratio and stock price